Integrating heterogeneous engineering knowledge and tools for efficient industrial simulation model support. Issue 3 (August 2015) - Novák, Petr; Serral, Estefanía; Mordinyi, Richard; Šindelář, Radek
Highlights The enhanced knowledge management improves the simulation design and integration. The article proposes a data model supporting simulation model engineering. An infrastructure called the Engineering Service Bus improves simulation processes. The approach is evaluated on a hydraulic system use-case showing its efficiency.